The application of the principles of precedent in the decision-making processes of planning and law - Blumenthal, Batya Brenda (My University, 2016)
This dissertaion will explore the principles of legal precedent and how they are applied in the legal decision-making process. This will take place in the framework of law and the South African legal system. The similar concerns of planning and law will be described. The nature of planning precedent and the way in which it is set and applied in principle and practice will be described. This will be compared to legal precedent and criticised accordingly. Case studies will be used to illustrate the practlcal ways in which planning precedent is created. All discussions will take place in terms of the notion of the pUblic interest as it is viewed from the perspective of the public sector planner. The growth and development of Planning and planning legislation will be traced to illustrate the public interest nature of planning. The dissertation will conclude with a set of recommendations which serve to formalise the way in which planning precedent is set and used.
A dissertation submitted to the Faculty of Architecture, University Of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Town and Regional Planning Johannesburg, 1991
Keywords: City planning and redevelopment law -- South Africa.; Regional planning -- Law and legislation -- South Africa.